Conformation Polymorphism of Polyglutamine Proteins. Issue 6 (June 2018) - Feng, Xinran; Luo, Shouqing; Lu, Boxun
Abstract : Expanded polyglutamine (polyQ) stretches within endogenous proteins cause at least nine human diseases. The structural basis of polyQ pathogenesis is the key to understanding fundamental mechanisms of these diseases, but it remains unclear and controversial due to a lack of polyQ protein structures at the single-atom level. Various hypotheses have been proposed to explain the structure–cytotoxicity relationship of pathogenic proteins with polyQ expansion, largely based on indirect evidence. Here we review these hypotheses and their supporting evidence, along with additional insights from recent structural biology and chemical biology studies, with a focus on Huntingtin (HTT), the most extensively studied polyQ disease protein. Lastly, we propose potential novel strategies that may further clarify the conformation–cytotoxicity relationship of polyQ proteins. Highlights: Structural basis of the cytotoxicity of soluble polyQ proteins is the key to understanding polyQ disease mechanisms. The 'linear lattice' model and the 'conformation emergence' model provide distinct explanations of the conformation–cytotoxicity relationship of polyQ proteins. The conformation 'polymorphism' of polyQ proteins is a key to reveal the conformation–cytotoxicity relationship of polyQ proteins. Recent studies on protein degradation rates of different mHTT species recognized by different polyQ antibodies provide strong evidence demonstrating the polyQ 'polymorphism'. Future studies of polyQ protein interactomes and post-translational modifications as well as polyQ protein–polyQ antibody complex structures may provide additional evidence demonstrating the polyQ 'polymorphism'.